Analyzing the Performance of Multi Seeds Smart Dryer (MSSD) with Low Cost and Low Energy Consumption (LCEC) - Indarto, Indarto; Pandunata, Priza; Nazdirah, Rufiani; Bahariawan, Amal; Sujarwo, Mohamad Wawan; Rahayu, Chairiyah Umi (Journal of Applied Agricultural Science and Technology, 2024)
Seeds drying technology is essential for ensuring the quality of agricultural products, particularly seeds. Although technological developments have resulted in more effective drying methods, challenges such as high energy consumption persist among small-scale farmers with limited resources. Therefore, this research aimed to analyze the performance of Multi Seeds Smart Dryer with Low Cost and Low Energy Consumption (MSSD-LCEC), a machine designed to solve the inadequacies of traditional seeds drying methods. The machine used low-energy components and environmentally friendly concepts to achieve sustainable seeds drying while remaining affordable for small-scale farmers. Using corn, peanuts, and soybeans as test materials, the performance of MSSD-LCEC was analyzed through the use of factors such as drying rate, energy consumption, temperature, humidity, and moisture content (MC). The results showed that the machine effectively dried seeds in acceptable MC levels, meeting quality standards for seeds certification. This research also discussed the economic benefits of MSSD-LCEC, highlighting the stable performance and efficient energy use. By optimizing the machine's operation and minimizing energy costs, small-scale farmers could enhance their profitability while contributing to environmental sustainability. In conclusion, further refinement of the control system had the potential to enhance both economic benefits and environmental sustainability in seeds processing applications.